The Relationship Between Perceived Stress, Body Image and Eating Behaviors in Athletes - Gökhan Deliceoğlu; İlknur Gökçe Yıldırım; Merve Atasoy; Gözde Şentürk (Research in Sport Education and Sciences)
The aim of the study was to evaluate the relationship between body image, eating behaviors, and stress states in athletes. The study was conducted with 72 volunteer athletes aged 13-23. The Perceived Stress Scale, the Dutch Eating Behavior Scale, the Multiphasic Body-Self/Self Relationship Scale and a questionnaire including questions about body weight satisfaction and emotional eating were applied to the athletes. Anthropometric measurements were taken using bioelectrical impedance analysis (BIA). The perceived stress levels of female athletes (28.29+-5.24) were found to be higher than those of males (24.34+-7.16). Restrictive and emotional eating behaviors were found to be higher in females. While the emotional eating subscale mean score was higher in taekwondo athletes (29.63+-14.213) than in rowing athletes (21.69+-10.058), the total body image score and physical adequacy orientation, health evaluation and health orientation subscale mean scores were higher in rowing athletes (p